2022
DOI: 10.3390/s22207885
|View full text |Cite
|
Sign up to set email alerts
|

Garage-Fabricated, Ultrasensitive Capacitive Humidity Sensor Based on Tissue Paper

Abstract: The role of humidity sensors in different industries and field applications, such as agriculture, food monitoring, biomedical equipment, heating, and ventilation, is well known. However, most commercially available humidity sensors are based on polymers or electronic materials that are not degradable and thus contribute to electronic waste. Here, we report a low-cost, flexible, easy-to-fabricate, and eco-friendly parallel-plate capacitive humidity sensor for field applications. The sensor is fabricated from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It is then fabricated using PET with small pores as a substrate, non-woven paper as a sensing layer for both the top and bottom sides, and copper tape as a sensing layer for both the top and an electrode because of its high electrical conductivity toward humidity. The sensor is garage-fabricated, as simple hands-on fabrication is done without the need for any such complex tools or devices, such as an inkjet printer, gravure printer, screen printing, or spin coating, which makes our sensor cost efficient in terms of electricity savings which are utilized by a fabrication process through these printers. , The comparison of normal PET and PET with small pores as a substrate is done, and it is experimentally verified that the sensor with the substrate having small pores is highly sensitive compared to the normal PET substrate. Figure shows the fabrication steps of the sensor, with PET having small pores as a substrate.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is then fabricated using PET with small pores as a substrate, non-woven paper as a sensing layer for both the top and bottom sides, and copper tape as a sensing layer for both the top and an electrode because of its high electrical conductivity toward humidity. The sensor is garage-fabricated, as simple hands-on fabrication is done without the need for any such complex tools or devices, such as an inkjet printer, gravure printer, screen printing, or spin coating, which makes our sensor cost efficient in terms of electricity savings which are utilized by a fabrication process through these printers. , The comparison of normal PET and PET with small pores as a substrate is done, and it is experimentally verified that the sensor with the substrate having small pores is highly sensitive compared to the normal PET substrate. Figure shows the fabrication steps of the sensor, with PET having small pores as a substrate.…”
Section: Methodsmentioning
confidence: 97%
“…Humidity sensors are enormously used to monitor the moisture content or water vapor concentration in the surrounding environment; nowadays, these sensors are used in different fields and commercial applications, including agricultural, food, medical, non-contact sensing, and space applications. , Different types of humidity sensors have been reported previously depending on their working principles, like resistive, impedance, capacitive, heater, or thermal techniques, and the change observed in their physical parameters after exposure to humidity. The most commonly used humidity sensors are resistive or capacitive. Resistance-based sensors have low cost, but the response is non-linear, has low performance, and cannot be used for sensitive applications.…”
Section: Introductionmentioning
confidence: 99%
“…60 Ullah et al reported a highly sensitive, flexible, and eco-friendly biodegradable nonwoven paper-based humidity sensor on polyethylene terephthalate (PET) substrate with copper tape as electrodes and demonstrated its applications in health and medicine. 61 In recent work, Li et al proposed a flexible humidity sensor based on alkalized MXenes and polydopamine for human−machine interaction in a noncontact manner. 62 Such studies suggest the emerging application of humidity sensors in determining human health severities related to respiration and skin moisture.…”
Section: Applications In Respiratorymentioning
confidence: 99%
“…Among these sensors, capacitive sensors with a dielectric layer sandwiched between two electrodes exhibit the advantages of a simple structure, facile manufacturing, low energy consumption, and static/dynamic detection. Therefore, flexible capacitive pressure sensors have attracted extensive attention in tactile sensing [ 16 , 17 ], environmental detection [ 18 , 19 ], and human motion monitoring [ 20 , 21 , 22 ]. High sensitivity is key to achieving high-pressure resolution, which is essential for simplifying signal processing [ 23 ].…”
Section: Introductionmentioning
confidence: 99%